A CROSS-SECTIONAL STUDY OF FACTORS ASSOCIATED WITH AGGRESSIVE BEHAVIOR AMONG FOURTH AND FIFTH GRADERS IN PALEMBANG - Lanny Tria Damayanti; Arie Kusumaningrum; Antarini Idriansari (Jurnal Keperawatan, 2026)
Aggressive behavior is intentional behavior, either physical or verbal, with the intent to hurt or harm others, caused by several factors. The aim of this research was to identify factors associated with aggressive behavior among fourth and fifth-grade students at SDN 111 Palembang, Indonesia. This research used a quantitative approach with a cross-sectional design. The population comprised 231 students in grades IV and V, with a sample of 101 respondents selected using cluster sampling technique. Data were collected using structured questionnaires and analyzed using the chi-square test with a significance level of α = 0.05. The results showed that 58 respondents (57.4%) were categorized as having high levels of aggressive behavior. There was a significant association between aggressive behavior and parenting style (p = 0.005), peer influence (p = 0.003), and playing violent video games (p = 0.007). However, no significant associations were found between aggressive behavior and snacking habits (p = 0.106) or exposure to violent media on television (p = 0.061). Aggressive behavior in children emerges as they become more exposed to external environmental influences that affect their cognitive and social development. Therefore, continuous monitoring by parents and teachers is necessary to control aggressive actions and recognize early signs of aggressive behavior in children.